Born As Subaltern or To Become Subaltern: An Exploration of Subalternity in Dana Johnson’s Because That’s Just Easier - Sardari, Alireza (Humanis; Vol 26 No 1 (2022)DO - 10.24843/JH.2022.v26.i01.p01, 2022)
The possibility to become subaltern in social relationships is an important issue in postcolonial studies. This article aims to investigate the representations of subalternity, and the characters’ reactions for being portrayed as subaltern in Dana Johnson’s story Because That’s Just Easier (2016). Spivak’s concept of subaltern will be consulted. Through the analysis process, I will introduce a process which I call ‘Normalization of Subalternity’ that spotlights the issue of subalternity in human relationships. The results indicate that subalternity is a social-cultural construct, not an overnight phenomenon. Two characters, that is, the man lying on the side walk and the six-year-old girl (Dakota) have both become subaltern because their suffering is the subject of others’ getting-used-to. The results also show that Dakota is expected and accepted to be vulnerable, but she deconstructs this mentality and rejects subalternity. She critiques her parents (and others alike) for getting used to the suffering of humanity.